Cellular and Molecular Evidence of Acetaldehyde Elimination and Intracellular Environment Antioxidation by L-Cysteine - Zhenjing Li; Xiaohong Zhang; Yibin Xue; Jingkai Zhang; Meiling Li; Cheng Luo (Journal of Chemistry)
Acetaldehyde is a harmful metabolite of smoking and drinking. This study was initially intended to facilitate the understanding of the possible injury mechanism of A549 cells damaged by acetaldehyde and the possible protective mechanism of L-cysteine (L-Cys) by analyzing the oxidative damage indicators, as well as the changes in cell morphology and gene expression. Results from the dithiodimorpholine nitrobenzoic acid colorimetric determination for glutathione peroxidase (GSH-Px) activity in L-Cys groups were significantly higher (P<0.01) than those in the acetaldehyde group in a dose-dependent manner. The expression of cytochrome c oxidase subunit II (COII) mRNA was significantly reduced compared with the control group (P<0.01) and was noticeably restored in the L-Cys groups. Scanning electronic microscopy observation, DAPI staining, and flow cytometry also indicated that L-Cys could effectively attenuate the oxidative damage to A549 cells caused by acetaldehyde and reduces the rate of apoptosis. In conclusion, the protective effects of L-Cys on A549 cells against oxidative damage by acetaldehyde were dose-dependent within the range of 10 μmol/L to 160 μmol/L. Acetaldehyde damaged the mitochondria and resulted in the apoptosis of A549 cells by reactive oxygen species (ROS), e.g., free radicals, but L-Cys reversed the release of cytochrome c from the mitochondria, reduced the rate of apoptosis, and protected cells from ROS and oxidative stress.